Református világnézeti nevelés - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
Reformed Confessional Education. This topic is of special interest because there have been several discussions, and debates based on the difference between ideologically neutral education vs. confessional education. Based on the five sola of the Protestant Reformation, the study classifies the main characteristics of the Reformed confessional education in three groups. A. Education and the principle of Solus Christus (“Christ alone”) Because of our Reformed identity we want to educate our children in a confessional way. Christ’s commandment „...go and make disciples of all nations, ... and teaching them to obey everything I have commanded you." (Matt 28:19–20) is the main reason for doing this. The Reformed education is based on two things, which can be seen also in the baptising liturgy: the education of a Christian child is the task of the family (parents) and of the community (Sunday school in parishes, schools). B. The biblical base of our world view is the principle Sola scriptura (“by Scripture alone”) Reading and studying the Bible is the base of the life of Reformed Christians. The greatest result of the Reformation was that the Bible became available for the whole population, as it was translated into many languages across Europe. Thus, the lowering of illiteracy was promoted. Reading the Bible alone or in community are both important, but it is more relevant that the children learn about the Holy Scripture being their main point of reference, as in any question it shows the right way in life (to use a modern metaphor, Bible should be their GPS). C. As a consequence of the principles Sola fide („by faith alone”) and Sola gratia (“only grace”) how do we understand and practice the Soli Deo gloria (“glory to God alone”) principle? The idea of acting out of gratefulness defines our world view (Heidelberg Catechism: Q&A 64.). It is clearly visible in work attitude, that we perceive it as God’s order and not as a punishment (see Genesis or the theory of Max Weber about the relationship of Capitalism and Calvinism). By education the message is that it doesn’t matter who we are, what our job is, but it is more important to live honestly, that our life would be Imitatio Christi, which regards to God. The last two parts of the study present the role, responsibility of the ones who educate: parents and teachers. In both cases the verbal transmission of contents, values can be successful only if the teacher is an authentic example of it. For this no one has to have superpowers, but honesty is an imperative, as children learn from the mistakes of the adults if they admit it, but double standards, discrepancy between what we say and what we do should be omitted. In ideal cases teachers and schools are lighthouses in children’s life which guide them.